Back Cover: Label‐Free Quantitative Proteomic Screening of Candidate Plasma Biomarkers for the Prognosis of Breast Cancer with Different Lymph Node Statuses. Issue 3 (2nd May 2018) - Chen, Ling; Zhao, Weibo; He, Jing; Li, Liqi; Meng, Dong; Cai, Dongyan; Yu, Jinjin; Chen, Daozhen; Wu, Yibo; Zhou, Tao
Abstract : Patients with lymph node involvement have less favorable prognosis and higher risk of recurrence. A label‐free quantitative proteomic strategy is applied to construct plasma proteomes of ten patients with different lymph node statuses. The present dataset provides a list of candidate biomarkers that can be used for early diagnosis and prognosis of breast cancer with lymph node metastasis. This is reported by Ling Chen, Weibo Zhao, Jing He, Liqi Li, Dong Meng, Dongyan Cai, Jinjin Yu, Daozhen Chen, Yibo Wu and Tao Zhou, article number 1700117.